Appropriate MRI Evaluation of Lisfranc Ligaments: How to Avoid Missing Ligamentous Lisfranc Injuries. Issue 1 (March 2019) - Bateni, Cyrus; Kahlon, Sukraj; Kreulen, Christopher
Abstract : Knowledge of injuries at the tarsal metatarsal joints continues to evolve. Fractures and ligamentous injuries at the tarsal metatarsal joints, also known as the Lisfranc joint complex, are uncommon yet can be of great clinical significance. The initial radiographic findings, suspected mechanism of injury, and physical examination findings can result in varying diagnoses and recommendations. Subtle or ligamentous injuries can be missed and result in the potential of midfoot instability and rapid progression to posttraumatic osteoarthritis. The imaging features of injury at the Lisfranc joint are reviewed, and guidance is provided as to the appropriate use and interpretation of weight bearing radiographs, computed tomography, and magnetic resonance imaging. This will include a description on the utilization of magnetic resonance imaging in evaluating ligamentous Lisfranc injuries to aid clinicians in successfully diagnosing a ligamentous or subtle injury.